Military regime transition to consolidated democracy in sub-Saharan Africa - Bimbiryte, Indre (KDI School, 2011)
During the last year the “Arab Spring” is capturing the world’s attention as a positive, albeit violent, fight against autocracy and dictatorships. However, a lack of democracy on the African continent remains high. Ghana is like an island of hope for the neighboring countries which are still ruled by the “iron fists” of their leaders, most of whom cover under the veil of feigned democracy. Having emerged from the military dictatorship, Ghana is an excellent example of a consolidated democracy for other Sub-Saharan nations. Starting as a fake democracy under the rule of Rawlings in the 1990s, Ghana eventually reached gradual democratization. The government has shifted powers already several times through free elections as the Ghanaian population actively took part in its country‘s rule. Free media and civil society continue to ensure the stability of democracy, as well as independent institutions that create steadiness in the process of consolidation. Ethnicity which most of the time creates tensions and remains one of the main issues on the African continent, in Ghana’s case can be seen as a factor that has a potential to further support the overall democratization.
Thesis(Master) --KDI School:Master of Public Policy,2011